Adrenal Insufficiency in Metastatic Lung Cancer - Carvalho, F (2015)
We report a case of adrenal insufficiency in patient with lung cancer. Although adrenal metastases are common in cancer patients, adrenal insufficiency is a rare occurrence. Diagnosis and treatment of adrenal insufficiency will improve the physical status and the quality of life in those patients.